Persepsi, Kesiapsiagaan, dan Adaptasi Masyarakat Kelurahan Aur Terhadap Ancaman Banjir Berulang Sungai Deli, Kota Medan - Amrullah Alayubbi Sinaga; Otniel Ketaren; Frida Lina Tarigan; Donal Nababan; Rinawati Sembiring (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research aims to analyze the perception, preparedness, and adaptation strategies of the community residing along the Deli Riverbanks in Aur Village, Medan, against the threat of recurring floods. This area is a densely populated settlement with high vulnerability to annual river overflows. The study employs a descriptive qualitative approach, with data collected through in-depth interviews with 11 informants, field observations, and documentation. The results indicate that community perception has undergone risk normalization, where small-scale flooding is perceived as a natural seasonal routine, thereby decreasing emotional vigilance. Regarding preparedness, the study reveals an absence of a formal Early Warning System (EWS) and limited standard evacuation equipment. However, the community has developed informal preparedness based on local knowledge and observations of natural signs. Adaptation strategies are implemented structurally through the construction of two-story or stilt houses and socially through the strengthening of social capital in the form of inter-neighbor solidarity and mutual cooperation (gotong royong) practices. This study concludes that community resilience in Aur Village is primarily supported by collective experience and strong social bonds rather than formal government infrastructure support.